(untitled) (Historia, 2021)
Oswald Pirow’s established place in South African historiography is that of a confirmed fascist, but in reality he was an opportunist. Raw ambition was the underlying motive for every political action he took and he had a ruthless ability to adjust his sails to prevailing political winds. He hitched his ambitions to the political momentum of influential persons such as Tielman Roos and J.B.M. Hertzog in the National Party with flattery and avowals of unquestioning loyalty. As a Roos acolyte he was an uncompromising republican, while as a Hertzog loyalist he rejected republicanism and national-socialism, and was a friend of the Jewish community. After September 1939 with the collapse of the Hertzog government and with Nazi Germany seemingly winning the Second World War, overnight he became a radical republican, a national-socialist and an anti-Semite. The essence of his political belief was not national-socialism, but winning, and the opportunistic advancement of his career. Pirow’s founding of the national-socialist movement, the New Order in 1940 was a gamble that “went for broke” on a German victory.